Feline parasites and the emergence of feline lungworm in the Portland metropolitan area, Oregon, USA 2016–2017. Issue 2 (October 2021) - Bishop, Greg T; DeBess, Emilio
Objectives: The aim of this study was to determine the prevalence of internal parasites in feral and free-roaming owned cats in the region of Portland, Oregon, USA. Methods: Fecal samples from asymptomatic cats were opportunistically collected from feral cats presented for surgical sterilization (n = 46), as well as free-roaming owned cats (n = 86) presented to primary care clinics. Fecal analysis was performed using the Baermann technique, centrifugal flotation, fluorescent auramine and fluorescent antibody for Giardia species. Results: Lungworm infection was identified in 24.2% of owned cats and 17.2% of feral cats. At least 11 unique parasite species were identified in this study. Taenia species and Toxocara cati were identified in higher proportions in feral cats, whereas Giardia species were significantly higher in owned cats. Conclusions and relevance: The prevalence of lungworm was higher than has been previously documented in other areas of the USA. In addition, feral cats were infected with a higher percentage of Toxocara species and Taenia but a significantly lower percentage of Giardia species.